Improving time-critical code performance with JNI - Kazymyr, V. V.; Karpachev, I. I. (Математичні машини і системи, 2016)
Analysis of usage of JNI for mobile devices with OS android is provided. JNI-workflow is explored including usage of code examples which realizes Java calls C and C++ parts of programs. Improving of performance due to replacing time-critical parts of code with JNI analogs is shown. Наведено аналіз використання JNI для мобільних пристроїв з ОС Android. Дослідження JNI-процесу проведено з наданням прикладів коду, що реалізує Java-виклики С і C ++ частин програм. Показано підвищення продуктивності за рахунок заміни критичних частин коду JNI аналогами. Приведен анализ использования JNI для мобильных устройств с ОС Android. Исследование JNI-процесса проведено с предоставлением примеров кода, реализующего Java-вызовы С и C ++ частей программ. Показано повышение производительности за счет замены критических частей кода JNI аналогами.